Custom-Made of ocular prosthesis for post enucleation: A Case Report - Novita Sari, Dian; Haryo Mustiko Dipoyono; Titik Ismiyati; Pramudya Aditama (Indonesian Journal of Prosthodontic, 2024)
Ocular prosthesis is part of a whole rehabilitative treatment plan after surgery. Stock ocular prosthesis, are premade, come in a range of colours and sizes with a right and left standard shape, and inexpensive to manufacture. The disadvantage is not being able to fit completely in the eye socket. To address this issue, the patients require a suitable prosthesis to enhance their living standards. A 75-year-old male patient came to RSGM UGM Prof. Soedomo using a stock ocular prosthesis. Complained that his ocular prosthesis loose and uncomfortable. The treatment plan was making custom-made ocular prosthesis using acrylic resin. The treatment procedure comprises minting the individual eye by using an individual tray; making the model of wax sclera followed by trying on the wax sclera pattern to the patient eye socket and continuing the acrylic resin process of sclera followed by trying on the eye socket, and then determining the location and iris diameter to draw the iris and pupil. The final step is inserting the ocular prosthesis into the patient’s eye socket. One week after insertion, the patient felt comfortable and has no complaints. Ocular prosthesis help improve the patient’s quality of life. Keywords: Custom-made ocular prosthesis, Rehabilitation, Enucleation